Identifying outbreak risk factors through case-controls comparisons - Nina H. Fefferman; Michael J. Blum; Lydia Bourouiba; Nathaniel L. Gibson; Qiang He; Debra L. Miller; Monica Papeș; Dana K. Pasquale; Connor Verheyen; Sadie J. Ryan (Communications Medicine)
Abstract Outbreaks are typically investigated using approaches that aim to identify place- and context-dependent causative factors. As the focus is on understanding the basis of a specific outbreak, the resulting narratives are rarely suitable for forecasting risk or developing generalizable predictive and preventative measures. This Perspective article proposes applying a case-control framework as an outbreak epidemiological study design to promote evidence-based decision-making for prevention and response to outbreaks. The approach involves identifying counterfactuals, with case-control comparisons drawn to test hypotheses about conditions that manifest outbreaks. First, a framework is described for iterative multidisciplinary interrogation to elucidate and identify minimally sufficient sets of factors that lead to disease outbreaks. Next, example case-control comparison frameworks are discussed, centered on pathogen(s), influential contributor(s), or landscape(s), illustrated with examples focused on pathogen transmission.